Case Report: Pituitary hyperplasia secondary to long-neglected severe primary hypothyroidism: a case of misdiagnosis and lessons learned - Du, Sina; Sun, Jiawei; Wang, Chunnuo; Zhou, Yanghuan; Zhao, Haiying; Li, Wei; Chen, Jianwei (Frontiers in Medicine, 2025)
BackgroundPrimary hypothyroidism is characterized by a loss of thyroxine feedback inhibition and an increase in thyrotropin-releasing hormone (TRH) levels, resulting in reactive pituitary hyperplasia. However, it is important to note that pituitary hyperplasia due to primary hypothyroidism (PHPH) is rare, particularly when symptoms of pituitary mass compression are present.Case summaryA patient with menstrual irregularities and hyperprolactinemia exhibited pituitary enlargement on magnetic resonance imaging (MRI). Initial treatment with bromocriptine mesylate failed, leading to surgical resection. Preoperative evaluation revealed severe hypothyroidism. Postoperatively, discontinuation of medication resulted in elevated thyroid-stimulating hormone (TSH) levels. Reticulin staining confirmed TSH hyperplasia, likely due to long-standing, untreated hypothyroidism since childhood. Postoperative thyroid hormone therapy restored normal thyroid and pituitary functions.ConclusionThis case underscores the importance of recognizing long-standing hypothyroidism as a potential cause of pituitary hyperplasia. Accurate diagnosis is essential to avoid unnecessary surgical or pharmacological interventions.